2013
DOI: 10.1159/000346675
|View full text |Cite
|
Sign up to set email alerts
|

Markers CD40, VEGF, AKT, PI3K, and S100 Correlate with Tumor Stage in Gastric Cancer

Abstract: Background: To better understand gastric cancer occurrence and prognosis, we explored the expression of molecules in the CD40 pathway and their correlation with gastric cancer prognosis. Patients and Methods: We measured the expression of CD40, VEGF, AKT, PI3K, and S100 in gastric cancer tissues and adjacent normal tissues from 128 patients by immunohistochemistry. Results: The expression of CD40, VEGF, AKT, and PI3K were significantly higher in tumor tissue than in normal tissue, while S100 expression in dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
12
0
1
Order By: Relevance
“…We confirmed its elevated expression by using IHC for detection of VEGF in gastric cancer tissues. Dysregulation of VEGF was reported to be through the PI3K‐Akt pathway in tumors [Ma et al, ; Shafee et al, ; Liu et al, ; Tian et al, ]. We observed that enforced BMP9 expression resulted in reduced expression of VEGF gene and protein in gastric cancer cells both in vitro and in vivo, and inhibition of the PI3K‐Akt pathway with LY294002 potentiated BMP9‐induced VEGF suppression.…”
Section: Discussionmentioning
confidence: 54%
“…We confirmed its elevated expression by using IHC for detection of VEGF in gastric cancer tissues. Dysregulation of VEGF was reported to be through the PI3K‐Akt pathway in tumors [Ma et al, ; Shafee et al, ; Liu et al, ; Tian et al, ]. We observed that enforced BMP9 expression resulted in reduced expression of VEGF gene and protein in gastric cancer cells both in vitro and in vivo, and inhibition of the PI3K‐Akt pathway with LY294002 potentiated BMP9‐induced VEGF suppression.…”
Section: Discussionmentioning
confidence: 54%
“…Patients testing positive for the abnormal expression of the PI3K/AKT/mTOR pathway were more likely to be in the late stages of gastric cancer with a lower survival rate. [4][5][6][7] Several drugs targeting PI3K/AKT/mTOR pathways are currently in clinical trials for gastric cancer, including PI3K inhibitor (LY294002, MK2206), AKT inhibitor (MLN1117), and mTOR inhibitor (everolimus). [8][9][10][11] PI3K inhibitor and AKT inhibitor monotherapy showed promising effects in Phases I-II, while mTOR inhibitor failed to improve survival in the GRANITE-1 Stage III trial for advanced gastric cancer.…”
mentioning
confidence: 99%
“…A score 4 was considered to be positive. 4,5,7 statistical analysis Statistical Package for the Social Sciences (SPSS) version 16.0 (SPSS Inc., Chicago, IL, USA) was used for the statistical analysis. The correlation between PI3K, p-AKT, and p-mTOR expression and patient clinicopathologic factors was analyzed using the χ 2 test.…”
mentioning
confidence: 99%
“…Another study also showed increased VEGF expression level in the advanced stages of GC compared to that in the earlier stages. 34 …”
Section: Discussionmentioning
confidence: 99%